PENGARUH PENDIDIKAN ENTREPRENEURSHIP, DUKUNGAN KELUARGA, LINGKUNGAN SEKOLAH, DAN PENGALAMAN ORGANISASI TERHADAP MINAT BERWIRAUSAHA MAHASISWA UNIVERSITAS BHINNEKA PGRI - Dwi Andriani, Ninis; Kadeni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the influence of entrepreneurship education, family support, school environment, and organizational experience on students' interest in entrepreneurship at Bhinneka PGRI University. This research uses a quantitative approach with associative methods. The sample consists of final semester students selected through proportional sampling techniques. Data was collected via questionnaire and analyzed using multiple linear regression. The research results show that simultaneously the variables of entrepreneurship education, family support, school environment, and organizational experience have a significant effect on students' entrepreneurial interest. However, partially only entrepreneurship education has a positive and significant effect, while family support, school environment and organizational experience do not show a significant effect. These findings reinforce the importance of education in encouraging students' entrepreneurial spirit.